2023
DOI: 10.1017/lsi.2022.103
|View full text |Cite
|
Sign up to set email alerts
|

Justices and Political Loyalties: An Empirical Investigation of the Supreme Court of the Philippines, 1987–2020

Abstract: The Philippine Supreme Court is considered one of Asia’s most activist courts. During the regime of President Rodrigo Duterte (2016–22), however, concerns grew about its independence. This article investigates determinants of the Court’s behavior since the country’s return to democracy in 1987, with particular attention to “loyalty effects”—the likelihood that justices will vote for the government more often when the president who appointed them is in office. Drawing on a data set of seventy major political ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Although our study may be the first to show increased loyalty during the Roberts Court years, we are not the first to uncover a loyalty effect among US Supreme Court justices (see, e.g.,Epstein & Posner, 2016); other studies have shown that the effect is not limited to the United States (see, e.g.,Dressel et al, 2023).…”
mentioning
confidence: 99%
“…Although our study may be the first to show increased loyalty during the Roberts Court years, we are not the first to uncover a loyalty effect among US Supreme Court justices (see, e.g.,Epstein & Posner, 2016); other studies have shown that the effect is not limited to the United States (see, e.g.,Dressel et al, 2023).…”
mentioning
confidence: 99%